2022
DOI: 10.1021/acs.jctc.2c00744
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic and Nonadiabatic Dynamics with Interacting Quantum Trajectories

Abstract: We present a quantum dynamics method based on the propagation of interacting quantum trajectories to describe both adiabatic and nonadiabatic processes within the same formalism. The idea originates from the work of Poirier [Chem. Phys. 2010, 370, 4–14] and Schiff and Poirier [J. Chem. Phys. 2012, 136, 031102] on quantum dynamics without wavefunctions. It consists of determining the quantum force arising in the Bohmian hydrodynamic formulation of quantum dynamics using only information about quantum trajectori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…We refer to [101-104, 108, 114, 140, 173]. Similarly, one should note that there exist approaches in the 'Lagrangian picture' 58 [51,87,138,155,166] and approaches based on the calculus of variations [64,72,108,183,184].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We refer to [101-104, 108, 114, 140, 173]. Similarly, one should note that there exist approaches in the 'Lagrangian picture' 58 [51,87,138,155,166] and approaches based on the calculus of variations [64,72,108,183,184].…”
Section: Discussionmentioning
confidence: 99%
“…Though Berry's example [19] is particularly illustrative, it is a well-known fact that not all L 2 -functions are weakly differentiable. Moreover, as neither dom Ĥ, H 1 0 (Ω, C), or even H 1 (Ω, C) are closed 51 We refer, for instance, to the beginning of section 8.4 in Brezis' book [35] for an example of how homogeneous Dirichlet boundary conditions are treated within the mathematical theory of PDEs. 52 Note that in [30] the authors considered the case dom Ĥ = H 2 0 (Ω, C) instead.…”
Section: Remark 35 (Hall's Criticism and Time-invariance Of Dom ĥ)mentioning
confidence: 99%
“…With respect to contraction schemes [39,40] or others basis set selections or pruning approaches [41], the Smolyak schemes enable to use selected basis sets and grids in a consistent way. [22,[42][43][44][45][46][47][48][49][50][51][52][53][54][55] Furthermore, in the second scheme, Smolyak has shown that a large direct-product can be substituted by a sum of small direct-products:…”
Section: Quantum and Quantum-classical Algorithmsmentioning
confidence: 99%
“…Furthermore, the D λ coefficients are (−1) L−|λ| C L−|λ| n−1 and C j i are binomial coefficients. However, in the present study, we have used constraints adapted to a system-bath separation [55] with three Smolyak parameters: (i) L b , a parameter associated to the bath modes (i…”
Section: Quantum and Quantum-classical Algorithmsmentioning
confidence: 99%
“…With proper sampling techniques, SCMC can produce accurate results with a moderate number of trajectories . Quasiclassical mapping is also a promising approach, which transforms the quantized electronic DoFs into fictitious continuous DoFs. ,, From the mapping Hamiltonian, a series of semiclassical approximations can be taken. , Based on the exact factorization formalism, the coupled-trajectory mixed quantum-classical (CT-MQC) dynamics provides another type of approximate trajectory-based method to investigate the electron-nuclei-coupled dynamics from a different perspective. ,,, Although these methods have achieved great success in different research fields, it is still difficult to achieve both high accuracy and low computational cost in complex systems.…”
Section: Introductionmentioning
confidence: 99%